Surface Water Pollution And Proposed Solutions For Quality Improvement In Kim Xa Commune, Vinh Tuong District, Vinh Phuc, Vietnam - Nguyen, Ha Thi; Nguyen, Khai Manh; Nguyen, Phuong Minh; Cai, Tú Anh; Nguyen, Tin Trong; Nguyen, Dat; Pham, Duong Khanh Thi; Vu, Ly Huong; Tran, Anh Quang; Le, Trang Quynh; Nguyen, Duong Thuy; Duong, Nhat Minh (International Journal of Biosciences and Biotechnology; Vol 1 No 1 (2023): Special Issue February (Online First), 2023)
The study investigated the current surface water pollution status in Kim Xa Commune, Vinh Tuong District, Vinh Phuc Province, in Northern Vietnam. Water samples were collected from Phan River, fish farms/ponds, and a pig farm’s effluent in Kim Xa Commune and analyzed for water quality parameters, including chemical oxygen demand (COD), total nitrogen (TN), total phosphorus (TP), and total suspended solids (TSS). Results showed that the Phan River water met the national water quality standards (Regulation QCVN 08:2015/BTNMT). However, the COD and TSS concentrations of the pond water and the piggery effluent exceeded their maximum permitted levels (QCVN 08:2015/BTNMT and QCVN 62:2016/BTNMT). Both had the highest COD of 145 and 192 mg/L, respectively. Moreover, the effluent’s TSS was 2.05 times higher than the national standard (QCVN 62:2016/BTNMT, column B). A 500 m2 floating treatment wetland system planted with water hyacinth has been proposed for improving the quality of the piggery effluent discharged to recipient drainage to meet the standards regulated in QCVN 08:2015/BTNMT for surface water